Severe acute respiratory syndrome in Singapore. Issue 6 (21st May 2004) - Puthucheary, J; Lim, D; Chan, I; Chay, O M; Choo, P
Abstract : Aims: To describe the epidemiological and clinical features of paediatric severe acute respiratory syndrome (SARS) in Singapore. Methods: The following data were retrospectively collected from the case records of all 71 patients (aged 7 months to 14 years) admitted from 23 March to 22 May 2003 to the SARS paediatric unit: patient demographics, contact history, clinical features, physiological parameters, investigations, treatment, and outcome. Using WHO criteria there were seven probable (P), 23 suspect (S), and 41 observe (O) cases. Results: Compared to the O cases P patients had a longer mean duration of fever (3.66 (SD 2.3) v 8.57 (SD 2.44) days), lower mean thrombocytopenia (248.3 (SD 82.7) v 173.7 (SD 49.0)×10 9 /l), leucopenia (8.19 (SD 4.45) v 3.06 (SD 1.02)×10 9 /l), lymphopenia (2.79 (SD 1.97) v 1.44 (SD 0.75)×10 9 /l), and neutropenia (4.48 (SD 2.88) v 1.24 (SD 0.43)×10 9 /l). Chest auscultation was abnormal in 71% of P patients, with mild crepitations detected. All had abnormal chest radiographs versus 39% of S cases, and 27% of O cases. Conclusions: There are no distinguishing clinical features of paediatric SARS. The diagnosis is suggested by the paucity of clinical signs with an abnormal chest radiograph, and laboratory evidence of leucopenia, lymphopenia, and thrombocytopenia.